Photoactivation of Endogenous Latent Transforming Growth Factor–β1 Directs Dental Stem Cell Differentiation for Regeneration - Praveen Arany; Andrew Cho; Tristan Hunt; Gursimran Sidhu; Kyungsup Shin; Eason Hahm; George Huang; James C. Weaver; Aaron Chen; Bonnie L. Padwa; Michael R. Hamblin; Mary Helen Barcellos‐Hoff; et al. (2014)
Low-power laser–activated endogenous latent transforming growth factor–β1 (LTGF-β1) directs resident dental stem cell differentiation to promote dentin regeneration.